Interpopulation variation in HIV testing promptness may introduce bias in HIV incidence estimates using the serologic testing algorithm for recent HIV seroconversion. - White, Edward; Goldbaum, Gary; Goodreau, Steven; Lumley, Thomas; Hawes, Stephen E (Sexually transmitted infections, 2010)
The serologic testing algorithm for recent HIV seroconversion (STARHS) calculates incidence using the proportion of testers who produce a level of HIV antibody high enough to be detected by ELISA but low enough to suggest recent infection. The validity of STARHS relies on independence between dates of HIV infection and dates of antibody testing. When subjects choose the time of their own test, testing may be motivated by risky behaviour or symptoms of infection and the criterion may not be met. This analysis was conducted to ascertain whether estimates of incidence derived using STARHS were consistent with estimates derived using a method more robust against motivated testing.
Keywords: Adult; Algorithms; Bias (Epidemiology); Enzyme-Linked Immunosorbent Assay; HIV Antibodies; HIV Infections; HIV Seropositivity; Humans; Incidence; Middle Aged; Washington; Young Adult